COMBATTANTS AND ANTICOMBATTANTS (COLLABOS): CONGOLESE TRANSNATIONAL POLITICS IN PRETORIA (The Strategic Review for Southern Africa, 2020)
This paper is concerned with the transnational political activities of Congolese nationals in Pretoria. The relationship between the migrants is marked by ethno-regional and political rivalry between two groups living in Pretoria, namely the 'combattants' and 'anti-combattants'. The paper argues that there is a dialectical interaction between Congolese transmigrant political activities, both in the Democratic Republic of Congo and in South Africa. These transnational political activities have an impact on both theCongolese and the South African political scenes. Most importantly, the intra-Congolese rivalry is not only intermittent, but some of its dynamics are influenced by local politics back in the Democratic Republic of Congo. Following ethnographic research conducted among Congolese migrants between 2011 and 2013, this study revealed that grassrootspolitical activists performed a key role in the Congolese transnational ethno-regional and political rivalry in Pretoria.
Keywords: transnational; political activities; Pretoria; Congolese nationals; migrants; ethno-regional; combattants; anti-combattants; dialectical interaction; Democratic Republic of Congo; South Africa; ethnographic research; Joseph Kabila